Human dental pulp stem cells exhibit enhanced properties in comparison to human bone marrow stem cells on neurites outgrowth. Issue 4 (25th February 2020) - Pagella, Pierfrancesco; Miran, Shayee; Neto, Estrela; Martin, Ivan; Lamghari, Meriem; Mitsiadis, Thimios A.
Abstract: Mesenchymal stem cells (MSCs) have the capacity to self‐renew and differentiate into specific cell types and are, therefore, key players during tissue repair and regeneration. The use of MSCs for the regeneration of tissues in vivo is increasingly being explored and already constitutes a promising alternative to existing clinical treatments. MSCs also exert paracrine and trophic functions, including the promotion of innervation that plays fundamental roles in regeneration and in restoration of the function of organs. Human bone marrow stem cells (hBMSCs) and human dental pulp stem cells (hDPSCs) have been used in studies that aimed at the repair and/or regeneration of bone or other tissues of the craniofacial complex. However, the capabilities of hBMSCs and hDPSCs to elicit the growth of specific axons in order to reestablish functional innervation of the healing tissues are not known. Here, we compared the neurotrophic effects of hDPSCs and hBMSCs on trigeminal and dorsal root ganglia neurons using microfluidic organs‐on‐chips devices. We found that hDPSCs express significantly higher levels of neurotrophins than hBMSCs and consequently neurons cocultured with hDPSCs develop longer axons in the microfluidic co‐culture system when compared to neurons cocultured with hBMSCs. Moreover, hDPSCs elicited the formation of extensive axonal networks and established close contacts with neurons, a phenomenon not observed in presence of hBMSCs. Taken together, these findings indicate that hDPSCs constitute a superior option for restoring the functionality of damaged craniofacial tissues, as they are able to support and promote extensive trigeminal innervation.